Exploring Attitude Resources in Percy Bysshe Shelley's Love's Philosophy: An Appraisal Theory Perspective - Ghina Aninnasi; Theofani Donita Padang; Nala Annisa Danin; Nurlela (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to analyze the realization of the Attitude system in Percy Bysshe Shelley’s poem Love’s Philosophy using the Appraisal framework in Systemic Functional Linguistics (SFL). This study employs a qualitative content analysis supported by frequency counts using documentation and close reading techniques to analyze the poetic text. Data were analyzed by identifying and classifying lexical-grammatical elements into three main subsystems: Affect, Judgment, and Appreciation. The results indicate that a total of 27 units of analysis were identified, with Affect and Judgment emerging as the most dominant subsystems, each accounting for 37% (10 data), while Appreciation contributes 26% (7 data). These three subsystems work collaboratively to construct the poem’s interpersonal meaning and persuasive power. Affect is characterized by expressions of desire and dissatisfaction reflecting the poet’s longing, while Appreciation highlights the harmony and beauty of nature as a justification for the value of love. Judgment is used to provide a moral evaluation of the rejection of love, which is positioned as a deviation from the laws of nature. These findings reveal that Shelley strategically utilizes natural phenomena as metaphors to reinforce the argument that unity is a universal law, thereby presenting love as something natural, obligatory, and inevitable through a balanced appeal to aesthetic beauty and ethical reasoning.